DRIVERS OF ACADEMIC CHEATING AMONG VOCATIONAL ACCOUNTING STUDENTS: THE ROLE OF MOTIVATION, SELF-EFFICACY, PROCRASTINATION, AND TECHNOLOGY MISUSE - Isnaini, Zahrofa Dinillah; Mardi; Respati, Dwi Kismayanti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study examines how learning motivation, self-efficacy, procrastination, and the misuse of information technology influence academic cheating among 11th grade accounting students in East Jakarta. These four variables were chosen because they represent essential internal and external drivers of academic behavior. Using a quantitative approach and proportional random sampling, with study population consisted of 180 students and sample size of 123 students. Data analysis was conducted using SPSS version 25, which included multiple regression analysis. The findings reveal that motivation and self-efficacy negatively affect cheating, while procrastination and technology misuse increase its likelihood. These results emphasize the importance of enhancing students’ intrinsic motivation and digital ethics to reduce dishonest behavior in vocational settings.